Long-term adoption of plow tillage and green manure improves soil physicochemical properties and optimizes microbial communities under a continuous peanut monoculture system - Yao, Yunfeng; Zhu, Rongyv; Li, Xiangdong; Hu, Guoqing; Dong, Yuanjie; Liu, Zhaoxin (Frontiers in Microbiology, 2025)
Continuous monocropping of peanuts (Arachis hypogaea L.) often results in yield decline and soil degradation. The combination of green manure (GM) with tillage practices has been proposed as a sustainable strategy to maintain high crop productivity and improve soil quality. This study investigates the long-term effects of 8 years of GM application combined with plow tillage on soil microbial communities and physicochemical properties under a peanut monocropping system. Treatments included: (i) no tillage (NT); (ii) plow tillage before the winter fallow period (PT); and (iii) growing ryegrass (Lolium perenne L.) during the winter period and applying it as GM before planting next-stubble peanut (PTGM). It was found that both PTGM and PT remarkably decreased the average bulk density (BD), while elevated the mean soil porosity (SP) in 0–30 cm soil layer. Moreover, PTGM significantly increased available potassium (AK), available phosphorus (AP), total nitrogen (TN), and soil organic matter (SOM). Peanut pod yields in the PTGM treatment were 14.1 and 7.2% higher compared to the PT and NT treatments, respectively. Additionally, PTGM could promote shifts in soil bacteria compositions, increasing the abundance of Actinobacteria and Firmicutes while reducing that of Chloroflexi. For fungal abundances, PTGM elevated the abundances of Ascomycota and Basidiomycote. Redundancy analysis demonstrated that SOM, TN, AK, and AP were positively related to dominant flora of fungi and bacteria in PTGM, while negatively related to dominant flora of fungi and bacteria in NT. Overall, tillage practices have the potential to reshape the microbial community during the peanut growing season, primarily due to the influence of SOM, TN, and AP content in shaping microbial diversity and composition. Our study highlights that plow tillage combined with GM application may serve as an effective tillage practice in the future to mitigate continuous cropping obstacles by modulating soil microbial communities, improving soil nutrients and fertility, and enhancing crop productivity.